O corpo leibniziano - Moura Lacerda, Tessa (2014)
Leibniz’s Discourse on Metaphysics (1686) is compared to his later work Monadology (1714) regarding the ontological status of corporeal substance. Although the body gains importance in the 1714 text, Leibniz has searched for its role within Metaphysics in 1686.